Integración de funciones hiperbólicas

RESUMEN TEÓRICO
    Enunciado
  1. Calcular $\displaystyle\int \cosh^2x\;dx.$
  2. Calcular $\displaystyle\int \operatorname{senh}^3x\;dx.$
  3. Calcular $\displaystyle\int \operatorname{senh}^3x\cosh x\;dx.$
  4. Calcular $I=\displaystyle\int \operatorname{senh}^2x\cosh^2 x\;dx.$
  5. Calcular $\displaystyle\int\tanh^3 x\;dx.$
    Solución
  1. Tenemos: $$\int \cosh^2x\;dx=\int \frac{1}{2}(1+\cosh 2x)\;dx=\frac{1}{2}\cosh x+\frac{1}{4}\cosh 2x+C.$$
  2. Si $t=\cosh x,$ entonces $dt=\operatorname{senh}x\;dx,$ por tanto: $$\int \operatorname{senh}^3x\;dx=\int \operatorname{senh}^2x \operatorname{senh}x\;dx=\int (\cosh^2x-1)\operatorname{senh}x\;dx$$ $$=\int(t^2-1)\;dt=\frac{t^3}{3}-t+C=\frac{\cosh^3x}{3}-\cosh x+C.$$
  3. Si $t= \operatorname{senh}x,$ entonces $dt=\cosh x\;dx,$ por tanto: $$\int \operatorname{senh}^3x\cosh x\;dx=\int t^3dt=\frac{t^4}{4}+C=\frac{\operatorname{senh}^4x}{4}+C.$$
  4. Usando $\operatorname{senh}x\cosh x=\dfrac{1}{2}\operatorname{senh} 2x$ y $ \operatorname{senh}^2x=\dfrac{1}{2}(\cosh 2x-1): $ $$I=\displaystyle\int (\operatorname{senh}x\;\cosh x)^2\;dx=\int\frac{1}{4}\operatorname{senh}^2 2x\;dx=\frac{1}{4}\int \frac{1}{2}(\cosh 4x-1)\;dx$$ $$=\frac{1}{8}\left(\frac{1}{4}\operatorname{senh}4x-x\right)+C=\frac{\operatorname{senh}4x}{32}-\frac{x}{8}+C.$$
  5. Tenemos: $$\int\tanh^3 x\;dx=\int\tanh^2 x\tanh x\;dx=\int(1-\operatorname{sech}^2x)\tanh x\;dx$$ $$=\int \tanh x\;dx-\int \operatorname{sech}^2x\tanh x\;dx=\log (\cosh x)-\frac{\tanh^2x}{2}+C.$$
Esta entrada fue publicada en Cálculo/Análisis. Guarda el enlace permanente.